2014
DOI: 10.1002/ccr3.48
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal phenotype of Williams–Beuren syndrome and of the reciprocal duplication syndrome

Abstract: Key Clinical MessageCopy losses/gains of the Williams–Beuren syndrome (WBS) region cause neurodevelopmental disorders with variable expressivity. The WBS prenatal diagnosis cannot be easily performed by ultrasound because only few phenotypic features can be assessed. Three WBS and the first reciprocal duplication prenatal cases are described with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Deletion of chromosome 3q29 region encompasses 22 genes, two of them ( PAK2 and DGL1 ) autosomal homologues of known X-linked genes associated with clinical features including intellectual disability, microcephaly, and mild dysmorphisms [19] . The prenatal diagnosis of the Williams-Beuren syndrome is even more challenging because only few phenotypic features can be investigated by fetal ultrasound, although FGR is present in most of them [20] . Finally, the haploinsufficiency due to terminal 15q26.2 deletion encompassing the IGF1R gene has been described to result in prenatal and postnatal growth failure, similarly to heterozygous mutation of the IGF1R gene [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of chromosome 3q29 region encompasses 22 genes, two of them ( PAK2 and DGL1 ) autosomal homologues of known X-linked genes associated with clinical features including intellectual disability, microcephaly, and mild dysmorphisms [19] . The prenatal diagnosis of the Williams-Beuren syndrome is even more challenging because only few phenotypic features can be investigated by fetal ultrasound, although FGR is present in most of them [20] . Finally, the haploinsufficiency due to terminal 15q26.2 deletion encompassing the IGF1R gene has been described to result in prenatal and postnatal growth failure, similarly to heterozygous mutation of the IGF1R gene [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…The prenatal phenotypes of Williams–Beuren syndrome and its reciprocal duplication have recently been described, but their prevalences were still unknown. In the present study, we found an incidence of 1:1156 (2/2311; 95%CI: 1/317–1/4213) for the microdeletion and of 1/2311 (95%CI: 1/409–1/13 091) for the microduplication in the high‐risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Williams-Beuren syndrome is a multisystemic neurodevelopmental disorder characterized by a distinct facial appearance, cardiac anomalies, cognitive and developmental anomalies, and connective tissue anomalies. Although prenatal diagnosis of this syndrome cannot be easily performed because only few of the phenotype features can be detected by ultrasound, FGR was present in most of the prenatal reports of this syndrome [26]. Interestingly enough, these three recurrent CNVs account for more than half of those found in nonmalformed fetuses with growth restriction, achieving a 2.4% prevalence in those fetuses.…”
Section: Discussionmentioning
confidence: 99%